Megaptera novaeangliae - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
8. Humpback Whale Megaptera novaeangliae French: Rorqual a bosse / German: Buckelwal / Spanish: Yubarta Other common names: Bunch Whale, Hump Whale, Hunchback Whale Taxonomy. Balaena novaeangliae Borowski, 1781, “de la nouvelle Angleterre,” (coast of New England, USA). Although there are no officially recognized subspecies, molecular evidence supports recognition of distinct populations in different ocean basins. Monotypic Distribution. Cosmopolitan, found in all oceans of the world, but with only rare incursions into the Mediterranean Sea. . Descriptive notes. Total length 1500-1700 cm; weight 30,000-34,000 kg. Adult female Humpback Whales are 40-70 cm longer than males. Mean lengths of physically mature males and females are 1300 cm and 1390 cm, respectively, while mean lengths at sexual maturity are 1180 cm and 1190 cm. The Humpback Whale is relatively shorter and stouter than any other species of rorquals and has a distinct countershading color pattern. Dorsal side of body is uniformly black, and ventral surface can be variably colored, ranging from black to white or mottled black and white. Some populations display an extension of white coloration up flanks. Underside of pectoral flipper typically is white, and color on dorsal surface can vary from all black in most Southern Hemisphere individuals to all white in most Northern Hemisphere individuals. Both lower lips are a uniform black and lack coloration asymmetry of the Fin Whale (B. physalus) and Omura’s Whale (B. omurai). Head of the Humpback Whale is relatively large, 28-30% oftotal body length. External surface of rostrum has a single, low, median ridge that is generally obscured by a series of fleshy knobs (dermal tubercles) that are spaced along it from blowholes to tip of snout. From above, lateral margin of rostrum of the Humpback Whale is slightly convex and intermediate in shape between the broadly U-shaped rostrum of the Blue Whale (B. musculus) and the more sharply pointed rostrum of the Fin Whale. In lateral view, rostrum of the Humpback ...